Revisiting India’s Amended Citizenship Act 2019 in Light of Constitutional Ethos - Jain, Shilpa; Srivastava, Ankit; Tiwary, Aditi Richa (University of Jember, 2022)
The Citizenship Amendment Act 2019 and the National Register of Citizens in India are perceived as reflective of a religious classification in grant and continuance of Indian citizenship. The study aimed to discuss the future effects of the amended Citizenship Act 2019 and suggest alternatives to accommodate India's constitutional ethos. A considerable fraction of the Indian citizenry was discorded with this Act because Article 14 of the Indian Constitution prohibits discrimination based on religion, among other grounds. On the other hand, the state's stance asserted that the law aims to protect the persecuted religious minorities from other states. This study dealt with the nuances and intricacies of the problem to explicate viable solutions by an in-depth analysis of the issue in an unprejudiced manner where it used a combined doctrinal and empirical research to assess the perspectives on the policy in the Global South from the Indian experience. The findings reflected that while a majority of the provisions in the Act can be justified based on constitutional parameters, its few provisions are unconstitutional. In summary, even after juxtaposing all the justifications of the Act against the allegations, a considerable portion of the Act remains unconstitutional, and it needs to be revisited based on constitutional parameters.Keywords: Citizenship Act, Indian Constitution, Right to Religion.